PENGARUH CASH FLOW, COMPANY GROWTH DAN PROFITABILITY TERHADAP INVESTMENT OPPORTUNITY SET - Teti Rahmawati; Rini Rahmawati (Program Studi Akuntansi, Universitas Kuningan, 2022)
This study aims to determine the effect of cash flow on the investment opportunity set, the effect of company growth on the investment opportunity set, and the effect of profitability on the investment opportunity set. The method used in this research is descriptive and verification methods with quantitative data types. The population in this study is the annual report of companies in the basic and chemical industry sectors, the various industrial sectors, the consumer goods industry sector, the infrastructure industry sector, and the trading sector listed on the Indonesia Stock Exchange in 2016-2019 as many as 183 companies with a sample of 75 companies. The data collection technique used is non-participant observation using a panel data regression test. Cash flow, company growth, and profitability simultaneously have a significant effect on the investment opportunity set. Cash flow has a significant positive effect on the investment opportunity set. Company growth has a significant positive effect on the investment opportunity set. Profitability has a significant positive effect on the investment opportunity set.Keywords: Cash Flow, Company Growth, Profitability, Investment Opportunity Set